Exploring group differences in the crossmodal correspondences - Spence, C (Brill, 2022)
There has been a rapid growth of interest amongst researchers in the cross-modal correspondences in recent years. In part, this has resulted from the emerging realization of the important role that the correspondences can sometimes play in multisensory integration. In turn, this has led to an interest in the nature of any differences between individuals, or rather, between groups of individuals, in the strength and/or consensuality of cross-modal correspondences that may be observed in both neurotypically normal groups cross-culturally, developmentally, and across various special populations (including those who have lost a sense, as well as those with autistic tendencies). The hope is that our emerging understanding of such group differences may one day provide grounds for supporting the reality of the various different types of correspondence that have so far been proposed, namely structural, statistical, semantic, and hedonic (or emotionally mediated).